The Street, Children and Parents: The Views of Children from Santiago de Chile - Vergara-Del Solar, A (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2023)
In this article, we present the partial results of a broader qualitative study carried out in the city of Santiago de Chile between 2016 and early 2020. In particular, we analyse the discourses found in 12 group interviews with Chilean children - aged 10 and 11, and of three socioeconomic strata (upper-middle, middle and low) - about the relationship they establish with the street s space and the negotiations they conduct with their parents about it. The results show that the street evokes a feeling of menace and moral downfall for the children, while parents are called on to play the role of protectors and moralisers. At the same time, the street is signified as a space of relative freedom, of peer sociability and play, to which they insist that parents give them access even though restricted. These results are closely linked to the socio-historical context in which modern childhood is constructed, the more recent media and political inflation of urban insecurity and the objectively hostile nature of urban environments for children.